Spunti Italiano elementare 2 - Leisawitz, Daniel; Viale, Daniela (Open textbook library., 2018)
Welcome to Spunti: Italiano elementare 2 – a new, unique program, authored by the Italian faculty of Muhlenberg College, that takes the place of a traditional language textbook. Spunti is a fully designed course that a college instructor of Italian can use and adapt.